Transcriptome analysis reveals the effects of sugar metabolism and auxin and cytokinin signaling pathways on root growth and development of grafted apple. (December 2016) - Li, Guofang; Ma, Juanjuan; Tan, Ming; Mao, Jiangping; An, Na; Sha, Guangli; Zhang, Dong; Zhao, Caiping; Han, Mingyu
Abstract Background The root architecture of grafted apple (Malus spp.) is affected by various characteristics of the scions. To provide information on the molecular mechanisms underlying this influence, we examined root transcriptomes ofM. robusta rootstock grafted with scions of wild-type (WT) apple (M. spectabilis ) and a more-branching (MB) mutant at the branching stage. Results The growth rate of rootstock grafted MB was repressed significantly, especially the primary root length and diameter, and root weight. Biological function categories of differentially expressed genes were significantly enriched in processes associated with hormone signal transduction and intracellular activity, with processes related to the cell cycle especially down-regulated. Roots of rootstock grafted with MB scions displayed elevated auxin and cytokinin contents and reduced expression ofMrPIN1, MrARF, MrAHP, mostMrCRE1 genes, and cell growth-related genesMrGH3, MrSAUR andMrTCH4 . Although auxin accumulation and transcription ofMrPIN3, MrALF1 andMrALF4 tended to induce lateral root formation in MB-grafted rootstock, the number of lateral roots was not significantly changed. Sucrose, fructose and glucose contents were not decreased in MB-grafted roots compared with those bearing WT scions, but glycolysis and tricarboxylic acid cycle metabolic activities were repressed. Root resistance and nitrogen metabolism were reduced in MB-grafted roots as well. Conclusions Our findings suggest that root growth and development of rootstock are mainly influenced by sugar metabolism and auxin and cytokinin signaling pathways. This study provides a basis that the characteristics of scions are related to root growth and development, resistance and activity of rootstocks.